THE IMPACT OF REHABILITATION ON THE QUALITY OF LIFE IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) - Aneta Rasińska,; Paulina Bala,; Justyna Matusik,; Piotr Rzyczniok,; Mateusz Kopczyński,; Justyna Jachimczak, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory condition characterized by airflow limitation and persistent respiratory symptoms, significantly impairing patients’ quality of life. Pulmonary rehabilitation (PR) has emerged as a comprehensive intervention aimed at improving physical and psychological outcomes. This narrative review aims to synthesize current evidence on the impact of rehabilitation on quality of life among individuals with COPD.Review Methods: A systematic search of recent literature was conducted using databases including PubMed, Scopus, and Web of Science. Peer-reviewed articles published within the last five years were selected based on relevance to pulmonary rehabilitation and quality of life outcomes in COPD. Both clinical trials and observational studies were included to provide a broad perspective.State of Knowledge: Rehabilitation programs, encompassing exercise training, education, and psychosocial support, consistently demonstrate improvements in exercise capacity, dyspnea reduction, and health-related quality of life (HRQoL). Emerging evidence supports the integration of tele-rehabilitation as an accessible alternative, especially amid barriers such as pandemics or geographic limitations. The multidimensional benefits of rehabilitation extend beyond physical symptoms to include psychological well-being and social participation, highlighting its critical role in COPD management.Conclusion: PR significantly enhances quality of life in patients with COPD by addressing physical, psychological, and social dimensions of the disease. Continued research is essential to optimize program delivery, including personalized approaches and remote interventions, to maximize patient outcomes.